Efektivitas Media Pembelajaran Diorama Augmented Reality Terhadap Hasil Belajar Materi Daur Hidup Hewan Pada Anak Dengan Hambatan Pendengaran - Saragih, Fachry Yudha Prayoga; Marlina, Marlina; Damri, Damri; Taufan, Johandri (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Children with hearing impairments have difficulty understanding abstract Natural Science (IPA) material, especially the concept of animal life cycles, due to limited access to verbal information and minimal use of visual media that suit their learning characteristics. The main objective of this study was to measure the effectiveness of the use of Augmented Reality Diorama learning media on learning outcomes of animal life cycle material in children with hearing impairments. The research method was Single Subject Research (SSR) with an A-B-A design. This study involved one student with hearing impairment in grade IX of SLB Negeri Simalungun as the research subject. The data collection technique used a learning outcome test in each research condition. The frequency of questions answered correctly. Data analysis was carried out through visual graphic inspection, including examination of data in each condition (within-condition analysis) and comparison between conditions (between-condition analysis). The results of the study showed a significant increase in learning outcomes after the Augmented Reality Diorama intervention was implemented. This increase was seen from the increase in the percentage score of students' understanding of animal life cycle material compared to the score in the initial condition (baseline). improving learning outcomes of animal life cycle material in students with hearing impairments.